Evaluation of physical properties of clays mixed with silica sand - Akbar Firoozi, A.; Taha, M.R.; Asghar Firoozi, A.; Tanveer A. Khan (Fakulti Kejuruteraan ,UKM,Bangi., 2014)
This study examined the effects of heat treatment on two types of clays mixed with silica sand under laboratory conditions. Soils were subjected to three varied temperatures, i.e. 100, 250 and 500°C. The soil properties studied were Atterberg’s limits, optimum water content and unconfi ned compressive strength. Experimental results showed that the temperature greater than 100°C resulted in a reduction in Atterberg’s limits, optimum water content and unconfi ned compressive strength. For illite and silica mixture heating the soils at 500°C, liquid limit, plastic limit, optimum water content and unconfi ned compressive strength were reduced to 12%, 0%, 40% and 0%, and for kaolinite and silica mixture the above characteristics reduced to 18%, 0%, 50% and 0% respectively when matched to soil specimen’s properties at ambient temperature. Whereas maximum dry density for illite and kaolinite increased by 5% and 8% respectively for the two clays.